Can We Give Seated Users in Virtual Reality the Sensation of Standing or Even Walking? Do We Want To? - Zielasko, Daniel; Riecke, Bernhard E. (SeatedVR: 1st Workshop on Seated Virtual Reality at IEEE VIrtual Reality, 2020)
VR is often experienced in a seated position, similar to 3D video games, that almost exclusively are. The reasons for this are diverse and can go beyond just being more comfortable [18]. Interestingly, even when users are physically seated, often designers try to simulate standing and moving experiences, using head-bobbing and other ways to make users believe they are walking. Does this actually work? Can we get seated users to believe they are standing, walking, or even running? Moreover, is trying to provide the illusion of being standing or moving while being seated even relevant and helpful? Does it improve user experience or performance? Or might it be more effective just to be ”honest” and ensure that the virtual locomotion metaphor matches the users’ physical posture? In this extended abstract, we aim to explore these little-researched questions and analyze different situations and scenarios, hoping to help motivate future research and discussion on this topic.
Keywords: 2-page conference paper; NSERC DG 2026; Riecke; Riecke_2020; bernhard-riecke; conferencePaper; conferencePapers; daniel-zielasko; locomotion; short conference paper